PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN ANGKA PENGANGGURAN TERHADAP TINGKAT KEMISKINAN DI DAERAH ISTIMEWA YOGYAKARTA - Prasetyo, Angger Gigih; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Special Region of Yogyakarta (DIY) is a province in Java with the highest poverty rate from 2012-2022, which is supported by the high Human Development Index (HDI) and the low unemployment rate with the Open Unemployment Rate (TPT) indicator. This study aims to determine the effect of HDI and TPT on the poverty rate in DIY, and also to find out the actual conditions in DIY Province by using the granger causality test method, panel data regression analysis and descriptive analysis. With this method, it results that there is no causality relationship between variables. For panel data regression analysis, the best model is Random Effect Model (REM) with the result that HDI has a negative and significant effect and unemployment rate has a positive and significant effect on poverty rate. Meanwhile, the actual condition of DIY is that the poverty rate in DIY is not like the statistical calculation of the Central Bureau of Statistics (BPS), because BPS statistical indicators cannot explain the poverty rate in DIY Province. The high poverty rate in DIY based on BPS is due to unique consumption patterns and is supported by the socio-cultural conditions that exist there.